COVID-19 Impacts on Women Factory Workers in Ethiopia : Results from High-Frequency Phone Surveys - Ajayi, Kehinde; Buehren, Niklas; Ebrahim, Menaal; Hailemicheal, Adiam (World Bank, Washington, DC, 2020)
As the Coronavirus 2019 (COVID-19) pandemic continues to disrupt international supply chains and local economies, workers employed in export-oriented industries are likely to experience both demand and supply shocks due to the crisis. In Ethiopia, a slowed global economy can pose a significant threat to the country’s industrial parks and their factories in the female-concentrated garment industry, forcing them to lay off workers or even shut down their operations. To monitor the potential effects of the pandemic and support the design of evidence-based policy responses, the gender innovation policy initiative for Ethiopia (GIPIE) is conducting a high-frequency phone survey on a sample of 323 recently hired female factory workers in Ethiopia. This brief reports on the first two waves of data collected between late March and late May 2020, showing the evolution of this sample of female workers’ employment status, earnings, and expectations over the course of the pandemic. Due to the size of the sample and the fact that it only includes recent hires at the Bole Lemi Industrial Park, the results may not generalize for the full population of women factory workers in industrial parks. Data collection from the ongoing high-frequency phone survey of women factory workers in Bole Lemi Industrial Park will continue in the coming months, with recurring surveys every month for a total of 6 rounds. By tracking the impacts of the COVID-19 pandemic, these data collection efforts aim to equip policymakers with timely, actionable data to better design and implement policy responses in support of Ethiopia’s women factory workers.